Polimorfismo HLA e Duffy em candidatos ao transplante renal da região Norte/Noroeste do Estado do Paraná - Yamakawa, Roger Haruki (2013)
The human leukocyte system (HLA) and the Duffy erythrocyte system are considered primary and secondary antigens of histocompatibility, respectively, and may be potential biomarkers for chronic kidney disease (CKD). In this study, we evaluated the HLA allelic polymorphism and antigens of Duffy in CKD patients waiting for a transplant. The HLA typing was performed, by the method of polymerase chain reaction-sequence specific primers (PCR-SSO), associated with Luminex technology. For the definition of Duffy phenotypes was used agglutination gel columns method with monoclonal antisera anti-Fya and anti-Fyb. In the first article, we studied the phenotypes Duffy, ABO and Rh in 231 renal patients. Among the patients studied, 46.3% were blood group O and 89.2% were positive Rh. There was no statistically significant difference in the frequencies between ABO and Rh patients and healthy subjects. The phenotype Fy(a+b+) was the most watched. There were statistically significant differences in the frequencies of Fy(a+b+) and Fy(a+b-) between patients and healthy subjects from the same region. In the second article, the polymorphism of the Duffy antigens and HLA allelic groups were studied in 183 patients. The phenotype Fy(a+b+) was the most watched. There were statistically significant differences in the frequencies of Fy(a+ b+) and Fy(a+b-) between patients and healthy subjects from the same region. The most frequent HLA allelic groups for each locus were: HLA-A*02 and -B*51 and -DRB1*11. When comparing the frequencies of HLA allelic groups of patients with healthy subjects, we found that the HLA-B*42, HLA-B*45,-B*51 and DRB1*03 were more frequent in patients (p <0.05) and HLA-B*44 in healthy subjects (p <0.05). This study allowed the knowledge of HLA allelic groups polymorphism and Duffy antigens in CKD patients waiting for a transplant. It was possible to observe the involvement of Duffy phenotype Fy(a+b-) and some HLA allelic groups in the DRC, suggesting some association between the expression of their antigens with the disease.